Difficulties encountered by computed tomography scan technologist in handling traumatic brain injury patient - A. Ingco, Schner; T. San Juan, Ronagene; P. Cacha, Daniele Clyde (Faculty of Medicine, 2026)
Traumatic Brain Injury (TBI) poses unique challenges in diagnostic imaging, especially for Computed Tomography (CT) scan technologists who managed difficulties related to patient positioning, communication, cooperation, and time constraints. This study aimed to identify the specific challenges encountered by CT technologists when handling TBI patients and examine whether demographic variables influence these challenges.